2012
DOI: 10.1038/onc.2012.350
|View full text |Cite
|
Sign up to set email alerts
|

Far upstream element binding protein 1: a commander of transcription, translation and beyond

Abstract: The far upstream binding protein 1 (FBP1) was first identified as a DNA-binding protein that regulates c-Myc gene transcription through binding to the far upstream element (FUSE) in the promoter region 1.5 kb upstream of the transcription start site. FBP1 collaborates with TFIIH and additional transcription factors for optimal transcription of the c-Myc gene. In recent years, mounting evidence suggests that FBP1 acts as an RNA-binding protein and regulates mRNA translation or stability of genes, such as GAP43,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 98 publications
1
116
0
Order By: Relevance
“…4,15); therefore, P89 expression should be critical for c-myc regulation through FIR (4,16). This study revealed that both total FIRs (authentic FIR and FIR splicing variants including FIRDexon2) and P89 expression were significantly activated in colorectal cancer tissues (T) compared with corresponding nontumor tissues (N; Fig.…”
Section: Tfiih/p89/ercc3/xpb Is Activated In Colon Cancer Tissuesmentioning
confidence: 92%
See 1 more Smart Citation
“…4,15); therefore, P89 expression should be critical for c-myc regulation through FIR (4,16). This study revealed that both total FIRs (authentic FIR and FIR splicing variants including FIRDexon2) and P89 expression were significantly activated in colorectal cancer tissues (T) compared with corresponding nontumor tissues (N; Fig.…”
Section: Tfiih/p89/ercc3/xpb Is Activated In Colon Cancer Tissuesmentioning
confidence: 92%
“…6B). At this point, c-myc expression should be tightly constrained when cells respond to certain stimulations (16).…”
Section: Discussionmentioning
confidence: 99%
“…42 FUBP1 promotes cell proliferation, survival and metastasis through up-regulating c-Myc and plays important roles in organ development, including lung, brain, and neural network development. 27,43,44 In contrast, FUBP1 was known to transcriptionally downregulate the expression of TNFa. 45 Interestingly, c-Myc is elevated in cystic tissues of various PKD models and TNFa is elevated in PKD2 +/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was known that, under normal physiologic conditions, FUBP1 primarily localizes in the nucleus, and that under stress conditions, such as in the presence of heat shock, viral infection, and oxidative stress, FUBP1 either stops entering the nucleus or translocates from the nucleus to the cytoplasm, resulting in cytoplasmic accumulation. 27 Interestingly, TGF-b1, which is upregulated in ADPKD, was also reported to induce translocation of FUBP1 from the nucleus to the cytoplasm. 58 The presence of a physical interaction between FUBP1 and eIF4E-binding protein 4EBP1 suggests the complex 3FI-FUBP1 located at the 39UTR of PKD2 mRNA is indeed connected, via 4EBP1, to the initiation complex located at the 59UTR of PKD2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation